Análise do impacto de geração distribuída na rede de distribuição - Lewandowski, Daniel Goulart (2023)
Currently there has been a growth in the number of distributed generation units, mainly photovoltaic panels, in consumers connected to the low voltage grid, this growth alters the functioning of the electrical power system. Thus, in this work a study was carried out in order to analyze some of these impacts and demonstrate through power flow, simulated in the OpenDSS program, the results of these changes. For this, a review was made of the effects that distributed generation will have on the electrical grid, as well as its current condition. After that, the simulation was made in the OpenDSS program, this simulator was used due to using the QSTS method, where state transactions are analyzed as well as the effect of control devices, these almost always present in distributed generation sources; the simulations showed the behaviors of the electrical system with and without distributed generation. From the results, a quantitative analyze was made of the effect was made.